2021
DOI: 10.1029/2021pa004246
|View full text |Cite
|
Sign up to set email alerts
|

Control Mechanisms of Primary Productivity Revealed by Calcareous Nannoplankton From Marine Isotope Stages 12 to 9 at the Shackleton Site (IODP Site U1385)

Abstract:  High-resolution coccolithophore record reveal upwelling-related primary productivity variations not previously described.  Multiproxy integration allows the assessment of the control by major atmospheric circulation changes at orbital and suborbital timescales.  Reductions in surface productivity during abrupt cold episodes is the result of upwelling limitation by hydrological changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 126 publications
(359 reference statements)
1
3
0
Order By: Relevance
“…This could have resulted in high surface productivity of SW Iberian Margin (Figure 6), a scenario similar to the modern (+) NAO‐like configuration, when the North Atlantic atmospheric circulation intensifies and the westerly wind system shifts northward (e.g., Alvarez et al., 2009; Barton et al., 2001; Coste et al., 1986; Pailler & Bard, 2002; Sousa & Bricaud, 1992; Vitorino et al., 2002). Our interpretations are in agreement with the earlier studies from the SW Iberian Margin proposing a similar scenario to explain the surface productivity changes during MIS 11 and MIS 9 interglacials (Amore et al., 2012; González‐Lanchas et al., 2021). Coupled ocean‐atmosphere general circulation model studies have also demonstrated that present‐day NAO‐like modes also operated in the past at orbital timescale (e.g., Lohmann, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This could have resulted in high surface productivity of SW Iberian Margin (Figure 6), a scenario similar to the modern (+) NAO‐like configuration, when the North Atlantic atmospheric circulation intensifies and the westerly wind system shifts northward (e.g., Alvarez et al., 2009; Barton et al., 2001; Coste et al., 1986; Pailler & Bard, 2002; Sousa & Bricaud, 1992; Vitorino et al., 2002). Our interpretations are in agreement with the earlier studies from the SW Iberian Margin proposing a similar scenario to explain the surface productivity changes during MIS 11 and MIS 9 interglacials (Amore et al., 2012; González‐Lanchas et al., 2021). Coupled ocean‐atmosphere general circulation model studies have also demonstrated that present‐day NAO‐like modes also operated in the past at orbital timescale (e.g., Lohmann, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…-based SST records than our SST records during the stadials, might be due to the preferential degradation of C 37:3 alkenones (e.g., Gong & Hollander, 1999;Kim et al, 2009;Rontani & Wakeham, 2008;Turich et al, 2013;Zabeti et al, 2010).…”
Section: Orbital To Sub-orbital Scale Variabilitymentioning
confidence: 67%
See 2 more Smart Citations